PENGEMBANGAN TERMINAL PENUMPANG TIPE B KM 6 KOTA BANJARMASIN - Muhammad Raihan Ahda; Gusti Novi Sarbini (UNIVERSITAS LAMBUNG MANGKURAT, 2026)
The Type B Passenger Terminal Km. 6 in Banjarmasin has been developed to enhance a more efficient, integrated, and sustainable transportation system. However, issues such as circulation conflicts between vehicles and pedestrians, lack of optimized public spaces, and limited integration with the surrounding environment persist, affecting user comfort and accessibility. To address these challenges, the Transit-Oriented Development (TOD) concept is applied, focusing on building mass and form, circulation and connectivity, and optimization of public spaces and social interaction. This concept is implemented to establish spatial order, improve circulation efficiency by separating vehicle and pedestrian pathways, and provide more comfortable and functional interaction spaces. With the adoption of this concept, the terminal is expected to enhance accessibility, reduce dependence on private transportation, and serve as an activity hub that functions not only as a transit point but also as a public spaces that supports social interaction and economic growth in Banjarmasin City.